Diagnostic Colonoscopy Leading to Perforated Appendicitis: A Case Report and Systematic Literature Review - Daniel Paramythiotis; Konstantinia Kofina; Vasileios Papadopoulos; Antonios Michalopoulos (Case Reports in Gastrointestinal Medicine)
Introduction. Intestinal perforation is a known complication after colonoscopy. However, appendiceal involvement with inflammation and perforation is extremely rare and only 37 cases of postcolonoscopy appendicitis have been reported so far. We describe a case of perforated appendicitis 24 hours after colonoscopy that was treated successfully in our Department. Case Report. A 60-year-old female patient underwent a colonoscopy during the investigation of nontypical abdominal pain without pathologic findings. 24 hours after the examination she presented gradually increased right lower quadrant abdominal pain and a CT scan was performed, showing an inflammation of the appendiceal area with free peritoneal air. Through laparotomy, perforated appendicitis was diagnosed and an appendectomy was performed. The patient was discharged on the tenth postoperative day in good health condition. Discussion. The characteristics of all cases reported in the literature are described, including our case. Perforated appendicitis soon after a colonoscopy is a rare, but serious complication; therefore, it is crucial to be included in the differential diagnosis of postcolonoscopy acute abdominal pain.